Biodiesel Dari Minyak Buta-Buta (Hura Crepitans Linn) Dengan Menggunakan Katalis Ni/Lempung - Ekadian Lestari Simatupang; Syaiful Bahri; Edy Saputra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Biodiesel is one of the alternative fuels as a substitute for fossil fuels synthesised from the transesterification reaction. The process of making biodiesel which using a homogeneous catalyst is costly for product separation process. Thus use of heterogeneous catalysts such as Ni/Clay catalyst was developed. This study aims to produce biodiesel from Hura crepitans Linn oil to determine best conditions of making biodiesel, determine the physical andchemical properties of biodiesel produced and studied the effect of the amount of Ni metal that has been impregnated on clay. In this process, the amount of oil use is 50 grams, 90 minute reaction time and concentration of catalyst 0.5%-b. Variations in reactants mole ratio oil : methanol 1 : 6, 1 : 9, 1 : 12, varying the amount of Ni metal 0%-b, 1%-b, 2%-b, 3%-b impregnated into the clay. The highest result biodiesel produced from Hura crepitans Linn oilwas 93.70% having mole ratio of oil : methanol 1 : 9 with Ni catalyst (3%). Physical properties obtained at biodiesl result density 884 kg / m3, kinematic viscosity 4.46 mm2/s,acid number 0.49 mg KOH/g sample and flash point is 185°C .Keywords : Biodiesel, Catalyst Ni / clay, Hura crepitans Linn oil